2021
DOI: 10.3390/ani11020256
|View full text |Cite
|
Sign up to set email alerts
|

The Age-Related Cryptosporidium Species Distribution in Asymptomatic Cattle from North-Western Spain

Abstract: An age-related distribution of Cryptosporidium species has been reported in cattle, with C. parvum being predominant in suckling calves, C. bovis and C. ryanae being predominant in post-weaned calves and C. andersoni being predominant in adults. However, variants to this pattern have recently been reported. Thus, fecal samples (n = 594) from asymptomatic cattle were collected in north-western Spain. Animals were classified as <1 month (G1), 1–2 months (G2), 2–12 months (G3), 12–24 months (G4) and >2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 80 publications
12
27
1
Order By: Relevance
“…Subtype IIaA17G2R1 was only observed before in the Netherlands with also with a similar frequency to that observed in this study, though two studies conducted in France river and sea waters reported the presence of this subtype on fish [44,104,105]. Subtype IIaA16G3R1 has been found in cattle in several European countries, such as Germany, Italy, Spain, Poland, and the United Kingdom [20,51,54,55,102,106]. Subtype IIaA17G2R1 has been found in cattle in Slovakia, Poland, Spain, Germany, and the United Kingdom [20,55,94,102,106,107].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Subtype IIaA17G2R1 was only observed before in the Netherlands with also with a similar frequency to that observed in this study, though two studies conducted in France river and sea waters reported the presence of this subtype on fish [44,104,105]. Subtype IIaA16G3R1 has been found in cattle in several European countries, such as Germany, Italy, Spain, Poland, and the United Kingdom [20,51,54,55,102,106]. Subtype IIaA17G2R1 has been found in cattle in Slovakia, Poland, Spain, Germany, and the United Kingdom [20,55,94,102,106,107].…”
Section: Discussionsupporting
confidence: 89%
“…In western mainland Europe, the IIaA15G2R1 subtype was previously described as the most prevalent in cattle [36,37,40,[42][43][44]. Similar observations were reported in other European countries, including Portugal, Italy, Spain, Germany, Czech Republic, Austria, Slovenia, and the United Kingdom [20,51,52,54,55,57,66,67,88] and in other parts of the world such as Japan and Uruguay [89,90].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar prevalence studies in Europe, employing nested PCR targeting the 18S gene, documented less overall occurrence of Cryptosporidium spp. with 44.5% in Spanish dairy and beef farms, 62.3% in dairy farms of Estonia [50,51] and, in the Czech Republic, 79.2% in calves and 30.4% in cows [52,53]. In Germany and Italy, following microscopy methods for Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%